OPERATIONAL SURGERY AND TOPOGRAPHIC ANATOMY: CLINICAL SIGNIFICANCE AND RESEARCH PERSPECTIVES - Suyunova Zamira Axatovna; Awaish Asim (TADQIQOTLAR, 2025)
Abstract Operational surgery and topographic anatomy represent fundamental disciplines in  medical  education  and  clinical  practice.  Their  integration  provides  essential knowledge for safe and effective surgical interventions. This study analyzes the role of topographic  anatomy  in  surgical  operations,  evaluates  teaching  methods,  and highlights its importance in minimizing intraoperative complications.